Implementation of Parenting and Home Visit Counseling Program to Increase Students Learning Motivation at PKBM Janji Baik - Zulfa Yustianuari; Hidayatullah Haila; Ahmad Fauzi (JURNAL PENDIDIKAN IPS, 2023)
This research aims to describe the implementation of the parenting counseling program at PKBM Janji and the increase in student learning motivation results after participating in the parenting counseling and home visit program at PKBM Janji Baik. The approach used is a qualitative approach with descriptive methods. The data collection techniques and guidelines used are observation, interviews and documentation. The data sources in this study consisted of 8 people, namely 1 head of PKBM Janji Baik, 1 head of the counselor division, 3 parents/guardians of students and 3 students. Based on the results of research that has been conducted, it shows that: (1) the implementation of the parenting counseling program has gone well and can provide benefits for parents in understanding the character and education of students. It is said to be going well because parents have implemented parenting in accordance with the indicators in the implementation of the parenting counseling program. (2) the implementation of the home visit program has gone well. It is said to be going well because the implementation of the home visit program is in accordance with the indicators for the implementation of the home visit program. (3) students' learning motivation can be said to be good. This can be seen based on existing indicators, starting from students who have the drive to learn to the goals they want to realize.